Night flight : Amelia Earhart crosses the Atlantic - Burleigh, Robert; Minor, Wendell (New York : Simon & Schuster Books for Young Readers, 2011)
An account of Amelia Earhart's dangerous 1932 flight across the Atlantic Ocean from Newfoundland to Ireland, in which she survived bad weather and a malfunctioning airplane. Includes a brief biography of the aviator.
"A Paula Wiseman Book."
Maps on endpapers.
Includes bibliographical references.
Notable/Best Books (A.L.A.)
School Library Journal
Wilson's Children
Keywords: Earhart, Amelia, -- 1897-1937 -- Voyages and travels -- Juvenile literature; Earhart, Amelia, -- 1897-1937.; Earhart, Amelia, -- 1897-1937.; Air pilots -- United States -- Biography -- Juvenile literature; Transatlantic flights -- Juvenile literature; Air pilots; Transatlantic flights; Women -- Biography; Air pilots -- United States -- Biography; Transatlantic flights; Women -- Biography; Picture books for children